Reversal of Early Central Retinal Vein Occlusion by Alleviating Optic Nerve Edema with an Intravitreal Dexamethasone Implant - Cho, Young Joo (The Korean Ophthalmological Society, 2014)
This case describes the reversal of early central retinal vein occlusion (CRVO) with disc swelling after intravitreal dexamethasone implant (Ozurdex) injection. A 44-year-old female presented with sudden-onset intermittent blurred vision in her left eye. Fundus examination revealed multiple retinal hemorrhages without macular edema (ME). Two weeks later, an increased number of retinal hemorrhages with severe disc swelling were noted with still no sign of ME. An intravitreal dexamethasone implant was injected. Five days later, there were improvements in disc swelling and retinal hemorrhage. One month later, her subjective visual symptoms were completely improved, and fundus examination revealed marked improvement along with almost complete resolution of disc swelling. Intravitreal dexamethasone implant injection may potentially change the natural course of CRVO progression and its various subsequent complications.